2020
DOI: 10.1016/j.scitotenv.2020.140840
|View full text |Cite
|
Sign up to set email alerts
|

Levels and sources of hourly PM2.5-related elements during the control period of the COVID-19 pandemic at a rural site between Beijing and Tianjin

Abstract: The effects of COVID-19 and its control were studied for a rural site in Xianghe. • PM 2.5-related elements were hourly measured during our study. • Dust, coal combustion and industrial sources decreased during the control period. • Beyond expectation, vehicle emissions increased during the control period. • Lowest reductions of industrial emission occurred for air masses from northeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…As such, investigating the changes in the chemical components of aerosols that occurred during this special period can deepen our understanding of the impact of anthropogenic sources on air pollutants in urban areas. To date, numerous studies have been carried out on the impact of the lockdown on air quality and on source apportionment of aerosols in the NCP and in Hubei Province ( Cui et al., 2020 ; Dai et al., 2020 ; Sun et al., 2020 ; Zheng et al., 2020 ); however, few studies have been conducted on the YRD. Given that emission sources, economic structures and meteorological patterns differ in different regions of China, the impact mechanisms of the lockdown policy on the distributions and sources of air pollutants were distinct in each region.…”
Section: Introductionmentioning
confidence: 99%
“…As such, investigating the changes in the chemical components of aerosols that occurred during this special period can deepen our understanding of the impact of anthropogenic sources on air pollutants in urban areas. To date, numerous studies have been carried out on the impact of the lockdown on air quality and on source apportionment of aerosols in the NCP and in Hubei Province ( Cui et al., 2020 ; Dai et al., 2020 ; Sun et al., 2020 ; Zheng et al., 2020 ); however, few studies have been conducted on the YRD. Given that emission sources, economic structures and meteorological patterns differ in different regions of China, the impact mechanisms of the lockdown policy on the distributions and sources of air pollutants were distinct in each region.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the variations in air pollutants due to the COVID‐19 pandemic. They revealed the variations of SO 2 , NO x , and PM 2.5 concentration from a regional perspective based on data from satellites (Bauwens et al, 2020; Zhang et al, 2020), ground‐based national environmental monitoring centers (Cui et al, 2020; Huang et al, 2020; Yuan et al, 2021), or model simulations (Huang et al, 2020; Wang et al, 2020). However, this is the first study that focuses on the BC variations from ground measurements during the COVID‐19 lockdown at the megacity level.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chen et al [31] state that the reduction in pollutant level (such as reduced PM 2.5 concentration) cannot be solely explained by alterations in primary emissions; instead, decreasing concentrations of nitrate (60%), ammonium (45%) and primary aerosols can also play an important role. In another study, the elements barium, copper, iron, potassium and zinc were found to be dominating PM 2.5 -related elements [48]. The presence of these elements, even during the lockdown period at a rural site between Beijing and Tianjin was attributed to the aging processes of elements after the emission of fireworks in the Chinese New Year Eve night and vehicular emission [48].…”
Section: Particulate Matter and Aerosolmentioning
confidence: 96%